The Case for Primary Salivary Rhabdomyosarcoma - Geltzeiler, Mathew; Li, Guangheng; Abraham, Jinu; Keller, Charles (Frontiers in Oncology, 2015)
Rhabdomyosarcomas of the parotid and submandibular glands have the histological appearance of a skeletal muscle tumor yet can be found in tissue with no striated muscular elements. We examine the potential cell-of-origin for rhabdomyosarcoma and whether salivary tumors represent primary malignancy or metastasis. We have previously established genetically-engineered mouse models of rhabdomyosarcoma. In these mice, rhabdomyosarcoma is only induced when a Pax3:Fox01 fusion oncogene is activated with concurrent loss of p53 function (for alveolar rhabdomyosarcoma) or loss of p53 function alone (for embryonal rhabdomyosarcoma) using Cre-lox technology. These mutations are only activated under the control of promoters specific for selected cell lineages, previously thought to be myogenesis-restricted. RT-PCR and immunohistochemistry for lineage-specific promoter gene products reveal these promoters are active in wild-type mouse salivary gland. Given that mouse rhabdomyosarcoma frequently originates in the salivary glands and these myogenic–related promoters are normally expressed in salivary tissue, a high likelihood exists that the salivary gland contains a cell-of-origin of this muscle-related cancer.